Distribution and Fractional Composition of Petroleum Hydrocarbons in Roadside Soils - Larysa Mykhailova; Thomas Fischer; Valentina Iurchenko (Applied and Environmental Soil Science)
Total petroleum hydrocarbon (TPH) concentrations and their fractional composition (medium fraction: n-alkane chain-length C15 to C27, heavy fraction: >C27) were determined at distances from 1 to 60 m from roads and at soil depths from 0.5 to 15 cm. The traffic intensities were up to 25000 vehicles per day. Soil TPH concentrations were highest within 15 m distance (665 and 3198 mg kg−1 at the windward and leeward sides, resp.), followed by a rapid drop to background values beyond (196 and 115 mg kg−1 in 60 m distance at the windward and leeward sides, resp.). The data variability was lowest at distances of 1 m and highest within tree plantations at distances of 15 m from the road. The TPH concentrations decreased with depth but were significantly higher than the background at all depths investigated. A principal component analysis revealed a positive relation between the medium-to-heavy fraction ratio and soil depth. A fractional differentiation of hydrocarbons with distance from road was not observed. It was concluded that the assessment of the potential of hydrocarbons to translocate, accumulate, or degrade in soil necessitates their subdivision into fractions based on their physicochemical and metabolic properties.